2015
DOI: 10.1126/science.1260972
|View full text |Cite
|
Sign up to set email alerts
|

Dermal adipocytes protect against invasive Staphylococcus aureus skin infection

Abstract: Adipocytes have been suggested to be immunologically active, but their role in host defense is unclear. We observed rapid proliferation of preadipocytes and expansion of the dermal fat layer after infection of the skin by Staphylococcus aureus. Impaired adipogenesis resulted in increased infection as seen in Zfp423nur12 mice or in mice given inhibitors of peroxisome proliferator–activated receptor γ. This host defense function was mediated through the production of cathelicidin antimicrobial peptide from adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
413
2
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(437 citation statements)
references
References 38 publications
12
413
2
10
Order By: Relevance
“…Resistin is expressed in monocytes and epithelial cells (26), and thus could also be involved in host defense against pathogenic infections. The bactericidal activity of resistin and its expression in adipose tissue are also consistent with the known role of adipocytes in producing antimicrobial proteins that protect the host from bacterial infection (32).…”
Section: Discussionsupporting
confidence: 55%
“…Resistin is expressed in monocytes and epithelial cells (26), and thus could also be involved in host defense against pathogenic infections. The bactericidal activity of resistin and its expression in adipose tissue are also consistent with the known role of adipocytes in producing antimicrobial proteins that protect the host from bacterial infection (32).…”
Section: Discussionsupporting
confidence: 55%
“…In addition, all RDEB mice were cocolonized with one or multiple additional bacteria (SI Appendix, Table S2). Furthermore, previous proteomic studies on RDEB skin had revealed a significant increase in abundance of the antimicrobial peptide Camp (3), which has been implicated to play an important role in defense against invasive Staphylococcus aureus infections (24). Thus, RDEB mice were able to respond to Staphylococcus aureus by increased production of antimicrobial peptides, yet the bacterial colonization was elevated.…”
Section: Elevated Bacterial Colonization Of Rdeb Skin Is Independent Onmentioning
confidence: 93%
“…In addition to its metabolic role as a depot of lipids and lipid-soluble vitamins, it has steroidogenic activity and synthesizes hormones and paracrine mediators that control appetite, lipid and carbohydrate metabolism and reproduction (Cinti 2012). Moreover, adipose tissue is involved in immune surveillance (Grant and Dixit 2015;Zhang et al 2015). This group of functions suggests that the adipose tissue depots act as an integrated metabolic, endocrine and immune organ of the body (Ferrante 2013;Galic et al 2010;Rosen and Spiegelman 2014).…”
Section: Introductionmentioning
confidence: 99%